STRUKTUR GEOLOGI DAN VULKANOSTRATIGRAFI; PENDEKATAN MODEL ELEVASI DIGITAL DAN CITRA LANDSAT 8 - Hari Wiki Utama (Jurnal Geofisika Eksplorasi, 2020)
Morphological change and deformation have been happen on natural landscape on volcanic complex. Their would been seen topography formation the give contour line expression, drainage pattern as especially character for understanding geological guideline such as structural geology and lithology. In the geological and geophysics on volcanic complex can use early methode with Digital Elevation Model (DEM) of research scale map and Landsat Image 8 for understanding structural geology and volcanostratigraphy. Research study on Arjuno Welirang Volcanic Complex, East Java, a part of active volcano in Indonesia. This study used scale map 1:25.000 wich analyzed of topography contour and drainage pattern for determination of geological feature as structural geology and volcanostratigraphy unit. Coherence of dense contour line is an igneous rock lava indicated, whereas distantly space contour line is an indicated of pyroclastic. DEM is a product extraction processes of contour topography. MED dan Citra Landsat 8 could help deliniaton of structural geology and volcanostratigraphy unit, which analyzed of morphology, drainage pattern, source of eruption, morphogenesis, and lithology remark. Based on both of image model on KGAW have dextral fault with oriented of northwestern-southeastern, sinistral fault with oriented of southwestern-northeastern, and then structural volcanic as caldera, crater, and debris avalanche. In the KGAW have five source of main eruption and the the other eruption surrounding of KGAW and their become is composed of volcanostratigraphy unit. Approach to using of DEM and Lendsat Image 8 are a part of early stage on for understanding structural geology and volcanostratigraphy on volcanic complex.